PENERAPAN MULTIMEDIA PEMBELAJARAN DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS XI IIS-2 MATA PELAJARAN AL QURAN HADITS DI MA UNGGULAN KH. ABD. WAHAB HASBULLAH TAHUN AJARAN 2019-2020 - Hayati, Hamidah (Universitas KH. A. Wahab Hasbullah, 2021)
Continuous technological developments in the world of education require educators to have the ability to manage and take advantage of existing technological developments. The use of this technology is expected to be an alternative for teachers in the selection of instructional media. The use of instructional media in the teaching and learning process can generate new desires and interests, generate motivation and stimulation of learning activities, and even bring psychological influences on students. So that it will greatly help the effectiveness of the learning process and delivery of messages and lesson content. This research to describe the learning achievement of the students of class XI IIS-2 MA Unggulan K.H. Abdul Wahab Hasbullah, described the application of multimedia in learning and described the increase in student achievement after the use of multimedia in learning. This type of research is a Classroom Action Research. The research design used the model of Kemmis and Mc Taggart. The research subjects were students of class XI IIS-2, totaling 47 students, all of whom were women. Data collection techniques using observation, tests, field notes, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the use of multimedia can improve the learning achievement of al-Qur'an hadith for students. The pre-action stage shows that the learning achievement of class XI IIS-2 students in the subject of al-Qur'an hadith is low. The class average score only reached 73.23 while learning completeness was 63.83% with the highest score of 92 and the lowest score was 60. In the first cycle, the class average score increased to 80.83 with an increase in student learning completeness by 17, 02% (initial conditions 63.83% increased to 80.85%). In cycle II, with the improvement and modification of learning multimedia, accompanied by management of group formation and the provision of rewards, student learning achievement increased by 14.89% (condition in cycle I 80.85% increased to 95.74%), while the average score the class average reached 95.72. Learning achievement in cycle II has met the indicators of success because more than 90% of students have reached the KKM